National Authority for Child Care-Regional Alternative Child Care Office (NACC-RACCO CARAGA) - Sanogal, Emily (JPAIR Multidisciplinary Research, 2026)
Adoption telling the disclosure of adoptive status to children is a relational-cultural process that shapes trust, belonging, identity coherence, and stigma reduction. While global research emphasizes early and open disclosure, most findings come from Western contexts. This study addresses the gap in collectivist societies like the Philippines, where indigenous values such as kapwa, hiya, and pakikiramdam influence disclosure practices. The Caraga Region provides a unique socio-cultural setting for this investigation. A sequential explanatory mixed methods design was employed. Quantitative phase: Surveys with 350–400 respondents tested direct effects of disclosure practices (timing, openness, narrative coherence) on identity outcomes. Qualitative phase: 36–48 purposively selected parents participated in interviews exploring cultural orientations, relational climates, and community support. Data analysis included regression, mediation, and moderation models, complemented by thematic coding of qualitative data. Ethical approval was secured from the IRB of Caraga State University (Protocol No. CSU-IRB-2025-014). Disclosure practices significantly predicted identity outcomes (trust, belonging, coherence, stigma reduction). Relational climate mediated disclosure effects, cultural orientations moderated outcomes, and community support enhanced belonging and reduced stigma. Integration of quantitative and qualitative findings validated adoption telling as both empirically measurable and culturally embedded, leading to the development of the Relational–Cultural Disclosure Theory (RCDT). Early, open, and coherent disclosure strengthens adoptees’ identity and reduces stigma when supported by a positive relational climate and community networks. RCDT situates adoption disclosure within Filipino indigenous psychology and communal traditions, contributing to global adoption scholarship.